Discrete Optimization Problem in Local Networks and Data Alignment - FIOL, M. A; YEBRA, J. L. A; ALEGRE, I; VALERO, M (IEEE transactions on computers, 1987)
This paper presents the solution of the following optimization problem that appears in the design of double-loop structures for local networks and also in data memory, allocation and data alignment in SIMD processors.